Pakistan : the formative phase, 1857-1948 - Sayeed, Khalid B., 1926- (Karachi ; New York : Oxford University Press, 1968)
This admirably written book analyses in a scholarly and impartial way a mass of material relating to the creation of Pakistan. Taking 1857 as the starting point, Khalid bin Sayeed relates the diverse factors which periodically heightened or lowered tension between the Hindus and Muslims of the subcontinent.
Sir Syed Ahmed Khan's remarkable achievements, the emergence of the Indian National Congress and the Muslim League, the partition of Bengal, the granting of separate electorates, the Khilafat Movement, and the last minute manoeuvrings of both sides as the prospect of Independence drew nearer, are all excellently told. Impacting on this entire complex set of events, for better or worse, is the policy of the British Government.
. The latter part of the book gives a clear and penetrating account of Pakistan's first year of independence and the role of Jinnah as Pakistan's Governor-General. Even thirty years after it was first published, Khalid bin Sayeed's scholarly study of the formative phase of Pakistan remains the definitive work for the period.
Pt. 1. Origins of Pakistan. 1. Conflicting Views About the Origin of Pakistan. 2. Anglo-Muslim Conciliation and the Beginnings of Hindu-Muslim Tension in India, 1857-1914. 3. Attempts at Hindu-Muslim Unity, 1916-40. 4. The Emergence of Pakistan - I. 5. The Emergence of Pakistan - II. 6. The Muslim League. Its Role and Organization -- Pt. 2. Continuation of the Viceregal System in Pakistan, 1947-8. 7. Jinnah's Appointment as Governor-General of Pakistan. 8. Constitutional and Political Powers of the Governor-General. 9. The Centre and the Provinces, 1947-8. 10. The Viceregal System and the Muslim Nationalist Movement.
Previous ed.: Karachi : Pakistan Publishing House, 1960.
Includes bibliographical references (p. 308-316) and index.
Keywords: Muslims -- India; Pakistan -- History; Pakistan -- Politics and government